2020
DOI: 10.1152/ajpendo.00473.2019
|View full text |Cite
|
Sign up to set email alerts
|

Lactational metformin exposure programs offspring white adipose tissue glucose homeostasis and resilience to metabolic stress in a sex-dependent manner

Abstract: We previously demonstrated that exposing mouse dams to metformin during gestation results in increased beta-cell mass at birth and increased beta-cell insulin secretion in adult male offspring. Given these favorable changes after a gestational maternal metformin exposure, we wanted to understand the long-term metabolic impact on offspring after exposing dams to metformin during the postnatal window. The newborn period provides a feasible clinical window for intervention and is important for beta-cell prolifera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 36 publications
(36 reference statements)
1
20
0
Order By: Relevance
“…Images were analysed using HALO analysis software (Indica labs, USA) using DenseNet AI Plugin classifiers (‘crown-like structures’ or CLS analysis) and the Vacuole Quantification tool (adipocyte cell size) adapted to the H&E-stained WAT sections. The estimated adipocyte number was calculated based on methods previously described [ 28 ] by dividing the total volume of gonadal WAT (estimated from the tissue weight and density of rodent visceral WAT) by the mean adipocyte volume derived from the cross-sectional area measured by HALO. The percentage adipocytes surrounded by CLS, a marker of adipocyte death [ 44 ], was calculated by normalising the number of CLS by the number of adipocytes per section.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Images were analysed using HALO analysis software (Indica labs, USA) using DenseNet AI Plugin classifiers (‘crown-like structures’ or CLS analysis) and the Vacuole Quantification tool (adipocyte cell size) adapted to the H&E-stained WAT sections. The estimated adipocyte number was calculated based on methods previously described [ 28 ] by dividing the total volume of gonadal WAT (estimated from the tissue weight and density of rodent visceral WAT) by the mean adipocyte volume derived from the cross-sectional area measured by HALO. The percentage adipocytes surrounded by CLS, a marker of adipocyte death [ 44 ], was calculated by normalising the number of CLS by the number of adipocytes per section.…”
Section: Methodsmentioning
confidence: 99%
“…We and others have shown that the programming effects of maternal obesity on male rodent offspring adiposity and adipose tissue function can be ameliorated by maternal exercise intervention [ 17 , 21 , 22 ]. Although the effects of early life exposure to metformin on offspring body composition have been reported in several rodent models [ 23 , 24 , 25 , 26 , 27 , 28 , 29 ], the effects of clinically relevant maternal metformin intervention exclusively during obese glucose-intolerant pregnancy (and not lactation) on offspring WAT have not been studied. Furthermore, growing evidence indicates that programming effects can be sexually dimorphic, with males and females responding differently or showing a different time course of response to a suboptimal in utero environment [ 30 ], highlighting the importance of including both male and female offspring in this study.…”
Section: Introductionmentioning
confidence: 99%
“…However, studies in humans demonstrated that though metformin was transferred into breast milk, the concentration of metformin in breast milk was generally low and did not affect blood glucose of infants [17,18]. Moreover, in a recently published study using a similar scheme of lactational metformin treatment with higher dose of metformin compared to our study, Zach and colleagues found that the metformin levels in offspring's plasma were very low or undetectable [19]. We therefore postulated that a direct effect of metformin levels in offspring's blood in our study should be minor and unlikely to contribute to the effects of lactational metformin treatment on offspring's metabolic phenotypes observed in our study.…”
Section: Discussionmentioning
confidence: 42%
“…We have previously demonstrated the ability of metformin exposure during lactation to program decreased offspring adiposity and protection from the effects of HFD rechallenge ( 20 ). We next wanted to understand the impact of metformin given to dams at the same time as lactational HFD on offspring metabolic outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Formaldehyde-fixed, paraffin sections of liver were cut at 5 μm. All tissues were stained as described previously ( 20 ).…”
Section: Methodsmentioning
confidence: 99%